RESEARCH DEVELOPMENT IN VOCATIONAL EDUCATION IN NIGERIA: CHALLENGES AND PROMOTION STRATEGIES - ADEOSUN; ADESOJI, TAOFEEK (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The purpose of this paper is to showcase the relevance of educational research developments in promoting vocational education in Nigeria. The paper noted that research development has not been rightly positioned in the scheme of things in Nigeria, and that has affected our educational system in not a small measure, vocational education inclusive. This has overtime led to many of our graduates from different vocational educational training institutes not only unemployable, but also difficult for them to be employers of labour. While conceptualising research as an integral part of any educational programme based on what previous researchers have documented in literature, the paper further explained the research characteristics and as well classified research into its various forms: basic, applied, action, experimental and descriptive. Challenges facing educational research in Nigeria were also not left out in the paper as they were vividly reviewed. That was also thoroughly discussed in the treatise was how advancement in educational research can lead to promotion of vocational education in Nigeria. The paper finally recommended amongst others that National Orientation Agency (NOA) and Non Governmental Organizations (NGOs) should intensify efforts to promote continuity in government policy or programmes by educating the politicians on the reasons why government policies should not suddenly change whenever there is a change in administration. The paper finally noted that for Nigeria as a nation to get it right in terms of developing vocational education, all the stake holders in the educational sector including government at all levels, managements of our various vocational training institutions, Non Governmental Organisations, instructors and the students themselves have active roles to play in ensuring that problems facing educational research become things of the past.